2018
DOI: 10.1891/2474-8684.2.1.33
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Race Perspective of Police Shooting of Unarmed Black Males in the United States: Implications for Social Work

Abstract: Recent high-profile killings of unarmed Black males underscore a stark reality in America: though Black men have the same constitutional rights as all other citizens of the United States, in practice their rights are often violated. The negative stereotype that all Black males are criminals has created an environment that perpetuates the killing of unarmed Black males by police officers as justifiable self-defense. In this article, critical race theory (CRT) provides a theoretical lens to examine and understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Critical race theory (CRT) originated out of legal studies and was inspired by social activists and academics, including W. E. B. DuBois, Dr. Martin Luther King, Jr., Malcolm X, Frantz Fanon, and the Black Panthers (Curry, 2020). The theory posits that racism is engrained within the infrastructure of social institutions (Siegel, 2020), including education, religion, healthcare, economics, housing, political arenas, and criminal justice, and attempts to maintain ideals of white supremacy by keeping melanated groups marginalized (Adedoyin et al, 2019;Curry, 2020;Moore et al, 2018). As noted by Janel George (2021), Khiarah Bridges observes the following: "CRT recognizes that racism is codified in law, embedded in structures, and woven into public policy".…”
Section: Critical Race Theory and Perpetrator Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Critical race theory (CRT) originated out of legal studies and was inspired by social activists and academics, including W. E. B. DuBois, Dr. Martin Luther King, Jr., Malcolm X, Frantz Fanon, and the Black Panthers (Curry, 2020). The theory posits that racism is engrained within the infrastructure of social institutions (Siegel, 2020), including education, religion, healthcare, economics, housing, political arenas, and criminal justice, and attempts to maintain ideals of white supremacy by keeping melanated groups marginalized (Adedoyin et al, 2019;Curry, 2020;Moore et al, 2018). As noted by Janel George (2021), Khiarah Bridges observes the following: "CRT recognizes that racism is codified in law, embedded in structures, and woven into public policy".…”
Section: Critical Race Theory and Perpetrator Perspectivementioning
confidence: 99%
“…As noted by Janel George (2021), Khiarah Bridges observes the following: "CRT recognizes that racism is codified in law, embedded in structures, and woven into public policy". According to Moore et al (2018), CRT includes the following tenets:…”
Section: Critical Race Theory and Perpetrator Perspectivementioning
confidence: 99%
“…A recent study found that the leading cause of death of young Black males in the United States was being killed by police (Khan, 2019). Public health advocates need to address the inhumane nature of police brutality and police killing of young Black males (Alang et al, 2017; Moore et al, 2018).…”
Section: Sociohistorical Context Of Black Male Victimizationmentioning
confidence: 99%
“…The discomfort that many feel around the subject of slavery can be explained in part by the dehumanizing and holocaustic nature of this enterprise [41]. While the dehumanization and trauma that characterized slavery and colonization of the people of African descent and continue to do so (see [16,29,43,44]) are indisputable, they do not fully account for the significance of slavery and colonialism. Slavery, an enterprise employed for the development of the United States and Europe, also depicts the entrepreneurial, technological, irrigation skills, innovation, and the ingenuity of the people of African descent [5,45].…”
Section: The Significance Of the History Of Slavery And Colonialismmentioning
confidence: 99%